Rare case study of a primary carcinoma of the petrous bone and a brief literature review. Issue 4 (25th September 2014) - Atallah, Ihab; Karkas, Alexandre; Righini, Christian Adrien; Lantuejoul, Sylvie; Schmerber, Sébastien
Abstract: Background: Temporal bone carcinoma is an aggressive tumor with multiple unconfirmed risk factors. Methods and Results: Herein, we present a rare case of a primary petrous bone carcinoma in a female patient (65 years old) with an irrelevant medical history. She presented a postauricular swelling that revealed a multilocular osteolytic cystic lesion of the mastoid portion of the temporal bone on the CT scan. The patient underwent resection of the lesion and pathological analysis revealed moderately to well‐differentiated squamous cell carcinoma. Postoperative radiotherapy was carried out. Until the present time, the patient shows complete remission on regular clinical and radiological follow‐up. Conclusion: Although no widely accepted strategy for managing temporal bone tumors exists, a review of the literature showed that surgery with or without radiotherapy is the treatment of choice. Preoperative assessment and accurate staging are vital in ensuring that the treatment is adequate for each disease stage. © 2014 Wiley Periodicals, Inc. Head Neck 37 : E45–E48, 2015